Stakeholder Analysis in the Management of the Biyonga Watershed (DAS) Gorontalo Regency-Gorontalo Province - Herlindah; Isra Cahayani Bahuwa; Zein Setiawan Kadir; Fitryane Lihawa; Iswan Dunggio (Universitas Muhammadiyah Palu, 2024)
Several factors cause damage to the watershed areas, such as changes in land cover, erosion, sedimentation, and the increase of critical land, which occurs almost throughout the Biyonga sub-watershed area. Another factor contributing to the damage of the Biyonga sub-watershed is the management of the Biyonga sub-watershed itself. The Biyonga sub-watershed is one of the priority sub-watersheds within the Limboto watershed. One proposed solution is to map the stakeholders involved in the management of the sub-watershed. This study aims to analyze the stakeholders involved in the management of the Biyonga sub-watershed. Stakeholder analysis is crucial to determine the implementation of policies and programs in the Biyonga sub-watershed area based on changes in the biophysical and socio-economic conditions of the watershed. Data collection methods include interviews and focused discussions. The analysis used in this study is stakeholder analysis and policy implementation analysis. Based on the analysis results, there are nine stakeholders involved in the management of the Biyonga watershed. These stakeholders include key players such as the Bone Bolango Watershed Management Agency (BPDAS), Sulawesi River Basin Agency II (BWS), Regional Development Planning Agency (Bappeda), Provincial Environmental and Forestry Service (DLHK) of Gorontalo, Environmental Service of Gorontalo Regency, Public Works and Public Housing Service (PUPR), and Forest Management Unit VI of Gorontalo. Meanwhile, the subject stakeholders consist of the community, NGOs, and universities.